Bidirectional equalization based on error propagation detection in long-range underwater acoustic communication. (11th June 2019) - Kim, Hyeonsu; Kim, Sunhyo; Choi, Jee Woong; Bae, Ho Seuk
Abstract: Bidirectional equalization is a typical equalization method that can compensate for the channel effectively using multichannel time-reversal combining followed by single-channel decision-feedback equalization. However, because conventional bidirectional equalization employs decision-feedback equalizers, performance can be significantly degraded if errors propagate. In this paper, we propose a method to improve the performance of bidirectional equalization by detecting error propagation and selecting the type of equalizer. The proposed method reduces the error rate by applying a decision-direct equalizer instead of a decision-feedback equalizer in the event of error propagation. Simulation results and analysis of experimental long-range communication data show that the proposed method produces superior performance in bidirectional equalization.